Retour sur une (d)ébauche : Une problématique communicationnelle du changement technique - Thierry Bardini (Tic & Société)
Here, I revisit my paper published in 1993 in Technologies de l’Information et Société, and entitled “Diffusionism, constructivism and technological frame: A sketch of a communication approach of socio-technological change.” I begin with a new look at the possibility of a theoretical synthesis of the diffusion of innovations with (constructivist) theories of the genesis of technological objects, before coming back to the aporia and criticism of one such theory, i.e. the actor-network theory (ANT). Rather than proposing a solution to those problems, I insist on some avenues for further thinking, hopeful that some theoretical dead-ends,  rather than being only obstacles, can also be the engine of thought.